2022
DOI: 10.1590/1980-220x-reeusp-2021-0398en
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for peripheral intravenous catheter-related phlebitis in adult patients

Abstract: Objective: To identify risk factors for peripheral intravenous catheter-related phlebitis in adult patients. Method: This is a post hoc analysis of a randomized clinical trial, totaling 1,319 patients. Demographic and clinical variables related to therapy and phlebitis were investigated. For data analysis, frequencies, measures of central tendency and dispersion were calculated, and Pearson’s chi-square test and Fisher’s exact test were used, with logistic regression, ROC curve, and Odds Ratio calculation (95… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 26 publications
2
17
0
Order By: Relevance
“…Seventy-seven percent did not wait for the antiseptic to dry, 62% performed back-and-forth movements, and 53% touched the insertion site after antisepsis. 15 INS recommends using the Aseptic Non Touch Technique (ANTT®) for PIVC insertion. This technique consists of a specific and comprehensive set of infection prevention actions that aim to protect patients from infection during invasive clinical procedures and management of medical devices.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Seventy-seven percent did not wait for the antiseptic to dry, 62% performed back-and-forth movements, and 53% touched the insertion site after antisepsis. 15 INS recommends using the Aseptic Non Touch Technique (ANTT®) for PIVC insertion. This technique consists of a specific and comprehensive set of infection prevention actions that aim to protect patients from infection during invasive clinical procedures and management of medical devices.…”
Section: Discussionmentioning
confidence: 99%
“…In all of them, the professionals dilated the vein using only the latex procedure glove. 15 In the scoping review on the same topic, the evidence gathered indicated that health care professionals do not follow a pattern of tourniquet use and do not comply with principles established in international guidelines. The lack of a pattern contributes to the contamination of the tourniquet and with potential implications for the quality, safety, and effectiveness of care.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, pain is an indispensable indicator of possible PVC-related complications. Nurses can visually verify some signs, but other symptoms reported by the patient may be considered less reliable, such as irritation, and potentially more related to a possible adverse effect of the administration of certain intravenous drugs (29,30) and not to PVC phlebitis. Irritation was the item of the Assessment dimension with the highest CV (100%) in this study.…”
Section: Assessment Dimensionmentioning
confidence: 99%